Impact of Increasing Freight Loads on Rail Infrastructure from Fracking Sand Transportation - Hesse, Damien Edward (My University, 2014)
The increased use of the hydraulic fracturing technique, used extensively in the United States, for oil and natural gas extraction, has significantly expanded the frac sand market and impacted freight rail corridors. This growth in the freight rail sector is expected to raise the operation and maintenance costs for the railroads due to the increase in heavy axle loads (HAL), traffic in million gross tons per year (MGT), and fouling from surface spillage. The impact of heavy axle loads has been studied in some detail; however, it is unknown how infiltration of frac sand into the ballast affects the deformation behavior of the track structure. The purpose of this study was to determine the extent that frac sand infiltration and subsequent moisture retention in the ballast structure increases deformation as compared to clean ballast. Three ballast, and three frac sand samples were used in this study, of which the following basic properties were characterized: particle size distribution, mineralogy classification, particle shape, bulk density, void ratio, particle shape, hydraulic conductivity, and soil water characteristic curves. These properties were used to optimize the large-scale cyclic triaxial (LSCT) test method. The results of HAL tests show an increased rate of strain accumulation averaging 0.07%/MGT for every 30 kip car load increase. The results of the surface spillage tests show an average increased rate of strain accumulation averaging 0.05%/MGT, 0.13%/MGT, and 0.31%/MGT for AREMA ballast #24, #4A, and #5 respectively, for a 7% increase in gravimetric water content. The results of the WiscRail? modeling shows similar results to the HAL and ballast type LSCT results. As the load increases, the maintenance cycles increased 50% to 100%. The type of ballast was simulated in the model and for AREMA #24, #4A and #5, the maintenance cycles increased from 50% to %300 percent, respectively. Both the LSCT and WiscRail? model results show that the two primary factors governing ballast and frac sand behavior are the load amount and the ballast type.